Impact of Pupil Aberrations on Wavefront Manipulation - Nobis Thomas (EDP Sciences, 2021)
A systematic and quantitative analysis is given of the impact of pupil aberrations on the imaging performance in wavefront manipulation applications using adaptive optical elements. For the practical case of rotationally-symmetric types of wavefront corrections, such as defocus or spherical aberration, analytical expressions of the induced aberrations are derived including their pupil and field dependence. Each aberration is thereby related to the specific pupil aberration present at the adaptive element. The results can be used to specify the acceptable amount of pupil correction required for a specific magnitude and type of wavefront manipulation.